Supply chain and logistics for COVID-19 vaccines: Challenges and opportunities - Shanay Rab; Afjal Hayat; Abid Haleem; Mohd Javaid; Mukesh Kumar Hasija (Apollo Medicine)
According to the history of vaccine development, no vaccine for infectious disease has ever been developed in a shorter time than COVID-19. With the enabling scientific efforts and governments support, few vaccines for the COVID-19 have been developed across the globe. Using the keywords COVID-19 or coronavirus and vaccine supply chain management, and review of the literature are conducted on the databases of PubMed, Scopus, and Google Scholar. Study, collected the most up-to-date information on the COVID-19 vaccine supply chain, and then assessed it to find potential challenges and opportunities. Our prior understanding of the structure and function of the coronavirus family has also contributed to the quick development of several vaccination technologies. However, there is still a long way to go in terms of actually getting the vaccinations to people, as well as others that are on the way. In 2021 and beyond, the complicated logistics of controlling the vaccine cold chain, combined with limited government funding to assist distribution, will make mass immunization difficult. We have identified various challenges and opportunities related to the supply chain and logistics for COVID-19 vaccines. The solution to these challenges would play a crucial role to enhance the health quality infrastructure across the world. The present study discusses the various aspects of the COVID-19 vaccine supply chain and logistics that make its biggest challenges. The scale and short time required for global vaccination will teach lessons not only to researchers and manufacturers but also to supply chain managers. Scientists, researchers, and diverse sectors have all also benefited from the influx of opportunities.